A new pharmacological approach based on remdesivir aerosolized administration on SARS-CoV-2 pulmonary inflammation: A possible and rational therapeutic application. (November 2020) - Contini, Carlo; Enrica Gallenga, Carla; Neri, Giampiero; Maritati, Martina; Conti, Pio
Abstract: The new zoonotic coronavirus (SARS-CoV-2) responsible for coronavirus disease (COVID-19) is a new strain of coronavirus not previously seen in humans and which appears to come from bat species. It originated in Wuhan, Hubei Province, China, and spread rapidly throughout the world, causing over 5, 569, 679 global cases and 351, 866 deaths in almost every country in the world, including Europe, particularly Italy. In general, based on existing data published to date, 80.9% of patients infected with the virus develop mild infection; 13.8% severe pneumonia; 4.7% respiratory failure, septic shock or multi-organ failure; 3% of these cases are fatal. Critical patients have been shown to develop acute respiratory distress syndrome (ARDS) and hospitalization in intensive care units. The average age of patients admitted to hospital is 57–79 years, with one third half with an underlying disease. Asymptomatic infections have also been described, but their frequency is not known. SARS-CoV-2 transmission is mainly airborne from one person to another via droplets. The data available so far seem to indicate that SARS-CoV-2 is capable of producing an excessive immune reaction in the host. The virus attacks type II pneumocytes in the lower bronchi through the binding of the Spike protein (S protein) to viral receptors, of which the angiotensin 2 conversion enzyme (ACE2) receptor is the most important. ACE2 receptor is widely expressed in numerous tissues, including the oropharynx and conjunctiva, but mostly distributed in ciliated bronchial epithelial cells and type II pneumocytes in the lower bronchi. The arrival of SARS-CoV-2 in the lungs causes severe primary interstitial viral pneumonia that can lead to the "cytokine storm syndrome", a deadly uncontrolled systemic inflammatory response triggered by the activation of interleukin 6 (IL-6), whose effect is extensive lung tissue damage and disseminated intravascular coagulation (DIC), that are life-threatening for patients with COVID-19. In the absence of a therapy of proven efficacy, current management consists of off-label or compassionate use therapies based on antivirals, antiparasitic agents in both oral and parenteral formulation, anti-inflammatory drugs, oxygen therapy and heparin support and convalescent plasma. Like most respiratory viruses can function and replicate at low temperatures (i.e. 34–35 °C) and assuming viral thermolability of SARS-CoV-2, local instillation or aerosol of antiviral (i.e. remdesivir) in humid heat vaporization (40°–41 °C) in the first phase of infection (phenotype I, before admission), both in asymptomatic but nasopharyngeal swab positive patients, together with antiseptic-antiviral oral gargles and povidone-iodine eye drops for conjunctiva (0, 8–5% conjunctival congestion), would attack the virus directly through the receptors to which it binds, significantly decreasing viral replication, risk of evolution to phenotypes IV and V, reducing hospitalization and therefore death.